The comet assay in Drosophila: analysis of in vivo and in vitro repair approaches over MMS induced DNA damage - Rodríguez, Rubén; Gaivão, Isabel; Aguado, Leticia; Espina, Marta; García-Martínez, Jorge; Sierra, L. María (Spanish Journal of Environmental Mutagenesis and Genomics, 2023)
The comet assay in Drosophila was used to study DNA repair of MMS induced DNA damage in somatic cells, specifically the roles of nucleotide excision repair (NER) system and Mus308 (dmPOLQ) protein, checking the value of the in vivo and in vitro comet repair approaches. We have used the mus201, mus308 and mus201;mus308 mutant strains and the wild-type efficient repair OK strain in these analyses. For both approaches, third instar larvae were treated in vivo, and the comet assays were performed with neuroblast cells from brain ganglia. For the in vivo approach, larvae from the different strains were treated with increasing MMS concentrations, and the solvent. In the in vitro approach larvae from the wild-type OK strain were treated with 1 mM MMS, and the solvent, and comet nucleoids were incubated with cell free protein extracts from the different strains. Results demonstrated that whereas both approaches allowed the detection of NER and Mus308 repair activities on MMS induced damage, only the in vitro one permitted the quantification of these activities, comparing them with that of the OK strain: considering the Tail DNA comet parameter, the repair activity of mus201 strain on MMS induced damage was 47% of the OK strain activity, whereas that of the mus308 strain was 63%. These results demonstrate that the in vitro comet repair assay is applicable in Drosophila and may be a useful tool to study DNA repair.